Directional control of neurite outgrowth: emerging technologies for Parkinson's disease using magnetic nanoparticles and magnetic field gradients. Issue 196 (9th November 2022) - Dhillon, K.; Aizel, K.; Broomhall, T. J.; Secret, E.; Goodman, T.; Rotherham, M.; Telling, N.; Siaugue, J. M.; Ménager, C.; Fresnais, J.; Coppey, M.; El Haj, A. J.; et al.
Abstract : A challenge in current stem cell therapies for Parkinson's disease (PD) is controlling neuronal outgrowth from the substantia nigra towards the targeted area where connectivity is required in the striatum. Here we present progress towards controlling directional neurite extensions through the application of iron-oxide magnetic nanoparticles (MNPs) labelled neuronal cells combined with a magnetic array generating large spatially variant field gradients (greater than 20 T m −1 ). We investigated the viability of this approach in both two-dimensional and organotypic brain slice models and validated the observed changes in neurite directionality using mathematical models. Results showed that MNP-labelled cells exhibited a shift in directional neurite outgrowth when cultured in a magnetic field gradient, which broadly agreed with mathematical modelling of the magnetic force gradients and predicted MNP force direction. We translated our approach to an ex vivo rat brain slice where we observed directional neurite outgrowth of transplanted MNP-labelled cells from the substantia nigra towards the striatum. The improved directionality highlights the viability of this approach as a remote-control methodology for the control and manipulation of cellular growth for regenerative medicine applications. This study presents a new tool to overcome challenges faced in the development of new therapies for PD.